Engaging patients and families in communication across transitions of care: An integrative review. Issue 6 (June 2020) - Bucknall, Tracey K.; Hutchinson, Alison M.; Botti, Mari; McTier, Lauren; Rawson, Helen; Hitch, Danielle; Hewitt, Nicky; Digby, Robin; Fossum, Mariann; McMurray, Anne; Marshall, Andrea P.; Gillespie, Brigid M; et al.
Highlights: Patient and family engagement in communication during transitions of care benefits all. A continuum of participation, from passive to active engagement is evident. Health professionals must be adequately educated to be more inclusive of patients and families. Patient engagement must commence early to identify values, goals, expectations and preferences. Abstract: Objective: To determine the current evidence about patient and family engagement in communication with health professionals during transitions of care to, within and from acute care settings. Methods: An integrative review using seven international databases was conducted for 2003–2017. Forty eligible studies were analysed and synthesised using framework synthesis. Results: Four themes: 1) Partnering in care: patients and families should be partners in decision-making and care; 2) Augmenting communication during transitions: intrinsic and extrinsic factors supported transition communication between patients, families and health professionals; 3) Impeding information exchange: the difficulties faced by patients and families taking an active role in transition; and 4) Outcomes of communication during transitions: reported experiences for patients, families and health professionals. Conclusion: While attitudes towards engaging patients and family in transition communication in acute settings are generally positive, current practices are variable. Structural supports for practice are not always present. Practice implications: Organisational strategies to improve communication must incorporate an understanding of patient needs. A structured approach which considers timing, privacy, location and appropriateness for patients and families is needed. Communication training is required for patients, families and health professionals. Health professionals must respect a patient's right to be informed by regularly communicating.